2022
DOI: 10.3390/en15228744
|View full text |Cite
|
Sign up to set email alerts
|

Production and Testing of Butyl and Methyl Esters as New Generation Biodiesels from Fatty Wastes of the Leather Industry

Abstract: Climate changes caused by the greenhouse effect make it necessary to look for new sources of energy. One of them is waste of a biological origin. They are often difficult to dispose of and such a process can be expensive. Increasingly, they are used to produce biofuels that can replace petroleum-based fuels. They are also an alternative to food-based biofuels. The aim of the work was to propose a method of using fatty waste generated in a plant dealing with tanning animal skins and to evaluate the properties o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…In this area, it is worth mentioning the following scientific and research works: Ding et al [28] investigated the use of natural gas in a diesel engine, Longwic and Sander [29] extensively studied mixtures of rapeseed oil containing n-hexane, and Labaj and Barta [30] investigated the possibility of using butanol in a diesel engine. Numerous scientific works focus on the study of biodiesel and its impact on exhaust emissions, including [31][32][33][34][35]. In research carried out by Imran and Saleh [36], it was shown that biodiesel from Cresson oil and mixtures with Iraqi diesel oil reduce engine thermal efficiency and heat release, as well as delay time and cylinder pressure, while exhaust gas temperature and fuel consumption during braking increase.…”
Section: Introductionmentioning
confidence: 99%
“…In this area, it is worth mentioning the following scientific and research works: Ding et al [28] investigated the use of natural gas in a diesel engine, Longwic and Sander [29] extensively studied mixtures of rapeseed oil containing n-hexane, and Labaj and Barta [30] investigated the possibility of using butanol in a diesel engine. Numerous scientific works focus on the study of biodiesel and its impact on exhaust emissions, including [31][32][33][34][35]. In research carried out by Imran and Saleh [36], it was shown that biodiesel from Cresson oil and mixtures with Iraqi diesel oil reduce engine thermal efficiency and heat release, as well as delay time and cylinder pressure, while exhaust gas temperature and fuel consumption during braking increase.…”
Section: Introductionmentioning
confidence: 99%